1988
DOI: 10.1067/mva.1988.avs0080674
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asymptomatic carotid disease: Results of duplex scanning in 348 unselected volunteers

Abstract: The risk of stroke in patients with asymptomatic carotid disease appears to be related to the presence of a high-grade stenosis. To determine the prevalence of such lesions, duplex scanning was performed on 348 unselected volunteers without symptoms who attended hospital-sponsored health fairs. There were 209 women and 139 men whose ages ranged from 24 to 91 years. Risk factors included hypertension (37%), diabetes (8%), and smoking (23%). One hundred seven subjects (31%) had evidence of extracranial carotid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 0 publications
1
11
2
Order By: Relevance
“…Handa et al [6]noted that the frequency of more than 25% narrowing was 26% in 132 Japanese patients carrying risk factors for atherosclerosis but without cerebrovascular disease. Nevertheless, the frequency of carotid artery stenosis more then 50% found in this study (4.5%) was similar to those demonstrated in previous ultrasonography studies ranging from 3 to 5% [4, 5, 6]. No comparative data were available on the intracranial artery diseases in subjects without stroke.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Handa et al [6]noted that the frequency of more than 25% narrowing was 26% in 132 Japanese patients carrying risk factors for atherosclerosis but without cerebrovascular disease. Nevertheless, the frequency of carotid artery stenosis more then 50% found in this study (4.5%) was similar to those demonstrated in previous ultrasonography studies ranging from 3 to 5% [4, 5, 6]. No comparative data were available on the intracranial artery diseases in subjects without stroke.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, detection of mild stenotic lesions would be severely affected by sensitivity and specificity of the technique used. The frequency of cervical carotid arterial stenotic lesions of 11.5% obtained in this study was lower than in previous studies [4, 5, 6]where high-resolution carotid ultrasonography was used. Colgan et al [4]reported that 107 (31%) of 348 unselected volunteers had evidence of extracranial carotid disease.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Several population studies have established that asymptomatic carotid stenosis is 0.5% in individuals >50 years of age, 4.5% between 50 and 79 years, and 10% in individuals >80 years of age [38,39,40,41,42]. Prevalence increases with age, and is 9% in women and 7% in men [43].…”
Section: Neurovascular Disease Markersmentioning
confidence: 99%